2018
DOI: 10.1093/mnras/sty3463
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for incompleteness due to transit multiplicity inKeplerplanet occurrence rates

Abstract: We investigate the role that planet detection order plays in the Kepler planet detection pipeline. The Kepler pipeline typically detects planets in order of descending signal strength (MES). We find that the detectability of transits experiences an additional 5.5% and 15.9% efficiency loss, for periods < 200 days and > 200 days respectively, when detected after the strongest signal transit in a multiple-planet system. We provide a method for determining the transit probability for multiple-planet systems by ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 70 publications
4
124
1
Order By: Relevance
“…This process continues until either five TCEs have been found, or the largest MES value is less than the detection threshold. Zink et al (2019a) showed that this type of masking will make higher multiplicity systems more difficult to detect, as nearby transits have the potential of being partially or fully hidden by this type of masking. However, removing the signal with a transit model is impractical.…”
Section: Terramentioning
confidence: 99%
See 1 more Smart Citation
“…This process continues until either five TCEs have been found, or the largest MES value is less than the detection threshold. Zink et al (2019a) showed that this type of masking will make higher multiplicity systems more difficult to detect, as nearby transits have the potential of being partially or fully hidden by this type of masking. However, removing the signal with a transit model is impractical.…”
Section: Terramentioning
confidence: 99%
“…The window function gives the probability (prob) that a certain period (P ) will meet the three transit minimum requirement for TCE consideration within the span (t span ) of the available light curve (von Braun et al 2009;Ballard et al 2010). This metric is an essential ingredient for occurrence measurements (Burke et al 2015;Zink et al 2019a;Bryson et al 2019), where all aspects of detection probability must be considered. If the data were seamless, without any masking, the equation can be found analytically:…”
Section: Window Functionmentioning
confidence: 99%
“…While this may occur in some cases, it seems unlikely to provide the explanation for the bulk of the population since essentially all of the Kepler planet hosting systems would need to have undergone dynamical instability and engulfed a planet. Dynamical instability can already be ruled out for systems with 5 or more planets (Pu & Wu 2015), which may account for more than 50 per cent of stars (Zink et al 2019) -too many for engulfment to be responsible for difference in refractory composition. Therefore, in the next section, we argue instead that the mass of dust trapped in the disc due to gap opening by the planets provides a natural explanation.…”
Section: Depletion Due To Rocky Planetsmentioning
confidence: 99%
“…Instead of these simple cuts, we compute the probability of detection for each planet following Burke et al (2015), who model the probability of detection using the Christiansen et al (2015Christiansen et al ( , 2016 completeness parametrization; we use the appropriate completeness function parameters for DR25. (We do not model the reduced detection efficiency of subsequent planets in the same system (Zink et al 2019) and discuss the effect on our results in Section 3.3.) See Appendix for an empirical exploration of detection efficiency.…”
Section: Comparison To Kepler Samplementioning
confidence: 99%